Addition chemistry of rod-shaped 1,6-dicyanohexatriyne: Regioselectivity control by the remote cyano function - Schermann, Günther; Vostrowsky, Otto; Hirsch, Andreas (European Journal of Organic Chemistry, 1999)
The addition of different alcohols, amines, thioalcohols, ethers, cycloalkanes, tin hydride, alkenes or alkadienes to 1,6-dicyano-1,3,5- hexatriyne (1) leads, with a pronounced regioselectivity, to a series of substituted 1-ene-3,5-diynes. The addition of alcohols, amines and thiols proceeds preferentially in a syn mode leading to diastereomers with an E configuration. The reaction with free radicals, on the other hand, proceeds in an anti addition mode. The [4+2] and [2+2] cycloadditions performed with 1 yielded unsaturated six- and four-membered ring adducts, respectively. The cyclobutene derivatives resulting from [2+2] cycloadditions underwent spontaneous electrocyclic ring-opening reactions with the formation of butadiene derivatives. Nucleophilic additions to form 1 lead exclusively to products where the donor atom is bound at C-1. All the reactions, except the formation of 19, showed an excellent regioselectivity with respect to the preferred addition to a terminal C≡C triple bond.